Dispensing synthetic green leaf volatiles in maize fields increases the release of sesquiterpenes by the plants, but has little effect on the attraction of pest and beneficial insects - von Mérey, Georg; Veyrat, Nathalie; Mahuku, George; Lopez Valdez, Raymundo; Turlings, Ted; D’Alessandro, Marco (My University, 2011)
Maize plants respond to feeding by arthropod herbivores by producing a number of secondary plant compounds, including volatile organic compounds (VOCs). These herbivore-induced VOCs are not only known to attract natural enemies of the herbivores, but they may also prime inducible defences in neighbouring plants, resulting in stronger and faster defence responses in these VOC-exposed plants. Among the compounds that cause this priming effect, green leaf volatiles (GLVs) have received particular attention, as they are ubiquitous and rapidly emitted upon damage. In this study, we investigated their effects under realistic conditions by applying specially devised dispensers to release four synthetic GLVs at physiologically relevant concentrations in a series of experiments in maize fields. We compared the VOC emission of GLV-exposed maize plants to non-exposed plants and monitored the attraction of herbivores and predators, as well as parasitism of the caterpillar Spodoptera frugiperda, the most common herbivore in the experimental maize fields. We found that maize plants that were exposed to GLVs emitted increased quantities of sesquiterpenes compared to non-exposed plants. In several replicates, herbivorous insects, such as adult Diabrotica beetles and S. frugiperda larvae, were observed more frequently in GLV-treated plots and caused more damage to GLV-exposed plants than to non-exposed plants. Parasitism of S. frugiperda was only weakly affected by GLVs and overall parasitism rates of S. frugiperda were similar in GLV-exposed and non-exposed plots. The effects on insect presence depended on the distance from the GLV-dispensers at which the plants were located. The results are discussed in the context of strategies to improve biological control by enhancing plant-mediated attraction of natural enemies.
Keywords: Green leaf volatiles; Maize; Priming; Herbivore-induced plant volatiles; Parasitoids; Spodoptera frugiperda